Commodity windfalls, polarization, and net foreign assets: panel data evidence on the voracity effect - Arezki, R; Bruckner, M (University of Oxford, 2011)
This paper examines the effects that windfalls from international commodity price booms have on net foreign assets in a panel of 145 countries during the period 1970-2007. The main finding is that windfalls from international commodity price booms lead to a significant increase in net foreign assets, but only in countries that are ethnically homogeneous. In highly ethnically polarized countries, net foreign assets significantly decreased. To explain this asymmetry, the paper shows that in ethnically polarized countries commodity windfalls lead to large increases in government consumption expenditures and political corruption. The paper's findings are consistent with theoretical models of the current account that have a built-in voracity effect.